Aplicación de la sección 13 inventarios de la NIIF para Pymes en la compañía Connila S.A. - Morán Ortiz, Mery Alexandra (2020)
The Company CONNILA S.A NILA Confecciones, Comercio y Diseño is a private company whose main activity consists of the manufacture of various types of clothing such as overalls, pants, blouses, skirts, jackets, uniforms, blouses among others. It is under the regulation of national supervisory and control agencies such as the Superintendence of Companies, Securities and Insurance (SUPERCIAS); the Internal Revenue Service (SRI), the Ministry of Labor and other agencies Municipal Government. This company is known nationwide for its quality of making uniforms for different clients such as DIFARE, BIC, etc. The inventories of materials and finished products, must be properly organized because of its importance within the entity. For the development of the case study called "Application of section 13 "Inventories" of the IFRS for SMEs in the company CONNILA S.A." is made by applying the descriptive methodology, which consists of interpreting the information derived from documentation and interviews with business personnel, which resulted in some relevant issues that could affect the company significantly by not being properly supervised and controlled.